2002
DOI: 10.1186/1471-2210-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anethum graveolens L. seed extracts on experimental gastric irritation models in mice

Abstract: Background: As a folk remedy, Anethum graveolens seed (dill) is used for some gastrointestinal ailments. We aimed to evaluate aqueous and ethanolic extracts of anti-ulcer and acute toxicity effects of the Anethum graveolens in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…Dill seed essential oil is used in perfumery to aromatize cosmetics, detergents, soaps, as carminative and for control of flatulence, colic, and hiccups in infants and children (Slupski, Lisiewska, & Kmiecik, 2005). Earlier, various pharmacological effects of dill seed essential oil such as anticancer (Zheng, Kenney, & Lam, 1992), antidiabetic (Panda, 2008), antisecretory (Hosseinzadeh, Karimi, & Ameri, 2002), cytotoxic to human lymphocytes (Lazutka, Mierauskiene, Slapsyte, & Dedonyte, 2001), diuretic (Mahran et al, 1992), antihyperlipidaemic (Yazdanparast & Alavi, 2001), and antihypercholesterolaemic activity (Tian, Ban, Zeng, Huang, & Wang, 2011) have been reported.…”
Section: )mentioning
confidence: 99%
“…Dill seed essential oil is used in perfumery to aromatize cosmetics, detergents, soaps, as carminative and for control of flatulence, colic, and hiccups in infants and children (Slupski, Lisiewska, & Kmiecik, 2005). Earlier, various pharmacological effects of dill seed essential oil such as anticancer (Zheng, Kenney, & Lam, 1992), antidiabetic (Panda, 2008), antisecretory (Hosseinzadeh, Karimi, & Ameri, 2002), cytotoxic to human lymphocytes (Lazutka, Mierauskiene, Slapsyte, & Dedonyte, 2001), diuretic (Mahran et al, 1992), antihyperlipidaemic (Yazdanparast & Alavi, 2001), and antihypercholesterolaemic activity (Tian, Ban, Zeng, Huang, & Wang, 2011) have been reported.…”
Section: )mentioning
confidence: 99%
“…(also called dill or "Pakchee Lao" in Thais), a vegetable, is commonly used for cooking in Southeast Asia. In addition, AG has been demonstrated to possess significant mucosal protective, antimicrobial, antigastric irritation, and antioxidant activities (Chaurasia and Jain, 1978;Möhle et al, 1985;Mahran et al, 1992;Faber et al, 1997;Yazdanparast and Alavi, 2001;Hosseinzadeh et al, 2002;Delaquis et al, 2002). Moreover, previous studies have shown that AG could stimulate milk production and change the estrous cycles (Monsefi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…19) The plant is native in Southwest Asia and is cultivated in Europe, India and the United States. Recent papers have reported that AGF has pharmacological effects including anti-bacterial activity, 20) anti-hypercholesterolemic activity, 21,22) regulatory effects on menstrual cycle, 19) and anti-secretory effects on gastric mucosa, 23) but, the antiinflammatory effects of the flower of the plant are unclear.…”
Section: )mentioning
confidence: 99%